Impunity in Guatemala: The State’s Failure to Provide Justice in the Massacre Cases - Nathanael Heasley, Rodger Hurley, Kara E. Irwin, Andrew H. Kaufman, Nadine Moustafa (My University, 2016)
This report examines the Guatemalan State’s failure to fulfill its legal duty to investigate and provide an effective remedy for violations of the right of life in the massacre cases. Beyond documenting this failure, this report identifies six specific obstacles that prevent the State from meeting its international obligations: intimidation of witnesses and officials, corruption of officials, incompetence of officials, inadequate resources and resource management, the lack of a definition of military secrets, and misuse and failure to utilize procedural mechanisms. The report identifies examples of these obstacles and offers solutions for overcoming them in the future.